2019
DOI: 10.1002/ejoc.201900530
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Porphyrinoids, BODIPYs, and (Dipyrrinato)ruthenium(II) Complexes from Prefunctionalized Dipyrromethanes

Abstract: The introduction of functional groups into the meso‐position of dipyrromethanes, boron‐dipyrromethenes (BODIPYs) and porphyrinoids, is of fundamental importance in designing such dye systems for material sciences or photomedicine. One route that has proven to be particularly useful in this respect is the nucleophilic aromatic substitution (SNAr) on porphyrinoids and their precursors carrying electron‐withdrawing substituents. To further expand this methodology, the potential of the 4‐fluoro‐3‐nitrophenyl and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 104 publications
(124 reference statements)
1
15
0
Order By: Relevance
“…Syntheses of heteroleptic metal complexes employing dipyrrinato ligands based on late transition metals, e.g., ruthenium(II), rhodium(III) and iridium(III), are known in the literature [21a, 23a,b, 26a, 29] . The synthesis of the dipyrrinato complexes typically involves reaction of the dipyrrins under basic conditions with a commercially available (dichlorido‐bridged) metal‐arene precursor [2a,b, 23b, 26a, 27a, 28d, 29a,b, 30] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Syntheses of heteroleptic metal complexes employing dipyrrinato ligands based on late transition metals, e.g., ruthenium(II), rhodium(III) and iridium(III), are known in the literature [21a, 23a,b, 26a, 29] . The synthesis of the dipyrrinato complexes typically involves reaction of the dipyrrins under basic conditions with a commercially available (dichlorido‐bridged) metal‐arene precursor [2a,b, 23b, 26a, 27a, 28d, 29a,b, 30] …”
Section: Resultsmentioning
confidence: 99%
“…In preparation for the following experiments, the meso ‐substituted dipyrromethanes 1 – 15 were synthesized according to known procedures published by us and others [28a,b,d,e, 33] . Dipyrromethanes can then be transformed into the dipyrrins via oxidation with a suitable oxidation agent [22b, 27a, 28d, 33, 34] . Here, dipyrromethanes ( 1 – 15 ) served as starting materials for the required dipyrrins (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the three latter molecular targets, meta -SF 5 -phenyl-substituted dipyrromethanes 37a – c , prepared in high yields (62%–80%) under standard TFA-catalyzed reaction conditions using appropriate pentafluorosulfanyl-bearing aryl aldehydes and surplus pyrrole, were the strategic intermediates (Figure 2). More recently, the same authors reported the efficient preparation, under similar standard conditions, of useful meso -aryldipyrromethane scaffolds 37d [49] and 37e [50] (in 92% and 87% yields, correspondingly), which were further functionalized and/or used as building blocks for the formation of other interesting BODIPY or porphyrinoid molecular species.…”
Section: Classic Synthetic Strategiesmentioning
confidence: 99%